Jesse H. Jones papers - Jones, Jesse H. (Jesse Holman), 1874-1956.
Correspondence, speeches, reports, congressional releases, subject file, newspaper clippings, printed matter, photographs, and other papers chiefly documenting Jones's service as director of the Reconstruction Finance Corporation and as U.S. secretary of commerce. Also pertains to his service as administrator of the U.S. Federal Loan Agency. Subjects include Texas and national politics, Jones's service during four presidential administrations from World War I through the Great Depression and to the end of World War II, Democratic Party affairs, the centennial of Texas statehood, supply issues pertaining to national defense during World War II, and personal affairs. Includes correspondence with presidents Woodrow Wilson, Herbert Hoover, Franklin D. Roosevelt, Harry S. Truman, and Dwight D. Eisenhower. Other correspondents include Bernard M. Baruch, James A. Farley, John Nance Garner, Carter Glass, Harry L. Hopkins, Howard Hughes, Cordell Hull, Will Rogers, Charles M. Schwab, Alfred Emanuel Smith, John W. Snyder, and Henry A. Wallace.
U.S. secretary of commerce and financier.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Baruch, Bernard M. -- 1870-1965 -- Correspondence; Eisenhower, Dwight D. -- 1890-1969 -- Correspondence; Farley, James A. -- 1888-1976 -- Correspondence; Garner, John Nance, -- 1868-1967 -- Correspondence; Glass, Carter, -- 1858-1946 -- Correspondence; Hoover, Herbert, -- 1874-1964 -- Correspondence; Hopkins, Harry L. -- 1890-1946 -- Correspondence; Hughes, Howard, -- 1905-1976 -- Correspondence; Hull, Cordell, -- 1871-1955 -- Correspondence; Rogers, Will, -- 1879-1935 -- Correspondence; Roosevelt, Franklin D. -- 1882-1945 -- Correspondence; Schwab, Charles M., -- 1862-1939 -- Correspondence; Smith, Alfred Emanuel, -- 1873-1944 -- Correspondence; Snyder, John W. -- 1895-1985 -- Correspondence; Truman, Harry S., -- 1884-1972 -- Correspondence; Wallace, Henry A. -- 1888-1965 -- Correspondence; Wilson, Woodrow, -- 1856-1924 -- Correspondence; United States. -- Department of Commerce; United States. -- Federal Loan Agency; Democratic Party (U.S.); Reconstruction Finance Corporation; Depressions -- 1929 -- United States; Economic assistance, Domestic -- United States; New Deal, 1933-1939.; World War, 1914-1918.; World War, 1939-1945.; World War, 1939-1945 -- Equipment and supplies; Texas -- Centennial celebrations, etc; Texas -- Politics and government -- 1865-1950.; United States -- Economic policy -- 1933-1945.; United States -- Politics and government -- 1901-1953.; Cabinet officers; Financiers